2020
DOI: 10.1016/j.copbio.2019.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating biological structure into machine learning models in biomedicine

Abstract: In biomedical applications of machine learning, relevant information often has a rich structure that is not easily encoded as real-valued predictors. Examples of such data include DNA or RNA sequences, gene sets or pathways, gene interaction or coexpression networks, ontologies, and phylogenetic trees. We highlight recent examples of machine learning models that use structure to constrain model architecture or incorporate structured data into model training. For machine learning in biomedicine, where sample si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…Our research further supports the utility of network analysis to reduce the biological complexity of input datasets by capturing robust signals, which can improve the predictive performances of ML tasks 10 , 11 . Recently, the PsycheENCODE Consortium embedded a regulatory network into a deep-learning model and demonstrated that functional genomic data improved the detection of gene-phenotype associations in neurological disorders 42 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our research further supports the utility of network analysis to reduce the biological complexity of input datasets by capturing robust signals, which can improve the predictive performances of ML tasks 10 , 11 . Recently, the PsycheENCODE Consortium embedded a regulatory network into a deep-learning model and demonstrated that functional genomic data improved the detection of gene-phenotype associations in neurological disorders 42 .…”
Section: Discussionsupporting
confidence: 64%
“…Interpretability of ML models is becoming increasingly important, especially when it comes to the high-stakes decision-making of healthcare 40 . To generate interpretable ML models, incorporation of biological structures, such as PPI networks, into the ML models assists in making comprehensive predictions 10 , 11 . Recently, Ma et al showed that the infusion of hierarchical structures of biological functions into neural networks accurately predicted cellular growth from genotypes 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, several groups are developing statistical learning methods that are augmented with experimental knowledge which benefits both computational and experimental communities [15] . From the computational side, including prior knowledge helps reduce overhead by biasing methods and parameters towards physical relevance [15b] . From the experimental side, these methods can provide a “blueprint” output and reduce false positives that can consume experimental resources to disprove.…”
Section: Currently Available Communication Catalystsmentioning
confidence: 99%
“…[51][52][53] Incorporation of prior biological knowledge not only improves the transparency and interpretability of the modeling approach but also reduces noise while increasing signal by meaningfully pruning redundant relationships between predictors. [54] Capsule Networks are a promising approach for grouping CpGs that harness their statistical interactions and relate the groupings of predictors to clinical and biological outcomes. [27] Capsule networks explicitly model the relationship between images or genomic information by its constituent parts, or capsules, by parameterizing pose matrices (unitary transformations), and then hierarchically associate each of these parts independently to higher-order targets of interest.…”
Section: Introductionmentioning
confidence: 99%